2018
DOI: 10.1186/s13054-018-2216-5
|View full text |Cite
|
Sign up to set email alerts
|

Hyperchloremia and postoperative acute kidney injury: a retrospective analysis of data from the surgical intensive care unit

Abstract: BackgroundWhether perioperative hyperchloremia can induce postoperative acute kidney injury (AKI) is controversial. We investigated the association between perioperative hyperchloremia and postoperative AKI in patients admitted to the intensive care unit (ICU) after surgery.MethodsWe performed a retrospective observational study of patients admitted to the surgical ICU at a single tertiary care hospital between January 2011 and June 2016. Our primary objective was to determine whether hyperchloremia or an incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 26 publications
2
15
1
Order By: Relevance
“…This study succeeds a previous study [18] that analyzed the medical records of patients in the surgical ICU at our institution from 2011 to 2016. The previous study reported that exposure to hyperchloremia in the postoperative period in the surgical ICU was not associated with the incidence of AKI.…”
Section: Methodssupporting
confidence: 73%
See 1 more Smart Citation
“…This study succeeds a previous study [18] that analyzed the medical records of patients in the surgical ICU at our institution from 2011 to 2016. The previous study reported that exposure to hyperchloremia in the postoperative period in the surgical ICU was not associated with the incidence of AKI.…”
Section: Methodssupporting
confidence: 73%
“…The difference in the results regarding positive fluctuations in Cl − between this study and our previous study is also interesting [18]. In our previous study, we found that hyperchloremia (>110 mmol L −1 ) was not associated with postoperative AKI in the surgical ICU, and there was a positive association in the increase from the preoperative Cl − (which was measured within 1 month prior to surgery) to the maximum Cl − measured 0–3 days postoperatively in patients with a CKD stage ≥3.…”
Section: Discussioncontrasting
confidence: 62%
“…Many studies have examined the impact of hyperchloremia on AKI in critically ill patients, but debate persists regarding the relation between hyperchloremia and the occurrence of AKI [5,6,23,30,31]. A study of severely septic patients in the ICU showed that hyperchloremia was common in these patients due to aggressive fluid resuscitation, but that neither hyperchloremia nor an increase in the serum chloride level was associated with an increased risk of AKI development within the first three days of ICU admission [23].…”
Section: Discussionmentioning
confidence: 99%
“…We read with great interest the recent paper by Oh et al [1] investigating the association between perioperative hyperchloremia and postoperative acute kidney injury (AKI) in a large population of postsurgical patients admitted to the intensive care unit (ICU). One of the conclusions was that a substantial perioperative increase in serum chloride levels may reflect a higher risk of AKI in patients with moderate-to-severe chronic kidney disease (CKD) [1].…”
mentioning
confidence: 99%
“…One of the conclusions was that a substantial perioperative increase in serum chloride levels may reflect a higher risk of AKI in patients with moderate-to-severe chronic kidney disease (CKD) [1]. …”
mentioning
confidence: 99%